The influence of four different anticoagulants on dynamic light scattering of platelets. Issue 2 (9th April 2014) - Raczat, T.; Kraemer, L.; Gall, C.; Weiss, D. R.; Eckstein, R.; Ringwald, J.
<x xml:space="preserve">Abstract</x> For testing of dynamic light scattering of platelets with ThromboLUX (TLX) in platelet‐rich plasma (PRP) derived from venous whole blood (vWB), anticoagulation is needed. We compared TLX score in PRPs containing citrate, ethylene‐diamine‐tetraacetic‐acid (EDTA), citrate‐phosphate‐dextrose‐adenine (CPDA) or citrate‐theophylline‐adenosine‐dipyridamole. Initial and late TLX scores were measured after 30–120 min or four to six hours, respectively. Compared with citrate, mean differences in initial TLX score were only significant for CPDA. Also, mean differences between initial and late TLX scores were only significant for CPDA. TLX failed to detect EDTA‐induced platelet alterations. The clinical relevance of TLX needs further studies.